Standards of Proof and Constitutional Protection of the Family: The Probative Accreditation Matrix Model for Family Relationships (MAP-RFH) - López Sánchez, Rogelio (2025)
The present article aims to propose an evidentiary test (composed of six modules) to establish non-marital family relationships, based on an epistemological methodology focused on facts (Gascón Abellán, Taruffo, and Ferrer Beltrán) translated into factual indicators (such as cohabitation, care, community of life and risks, patrimonial ties, publicity, and social recognition), as well as on socio-legal evidence (2010–2025). The results include a comparative analysis grounded in international law (the InterAmerican Court of Human Rights [IACtHR] and the European Court of Human Rights [ECtHR]) and in the national courts of countries around the world (Brazil, Mexico, Colombia, Spain, South Africa, India, and Canada). The conclusions establish standards of sufficiency for the proposed model (plausibility and a convincing explanation), as well as refutability and bias control, which are intended to serve as guidance for the reasoning of judicial decisions with a human-rights-based approach.